Evaluating the Effectiveness of Technology in Sports Injury Prevention: A Systematic Review - Utomo, Andy Widhiya Bayu; Ashari, Mohamad Ihsan; Septianingrum, Kartika (Jurnal Porkes, 2025)
Technological advances such as wearables, biomechanical analysis and artificial intelligence (AI) offer promising solutions in sports injury prevention. This study aims to evaluate the effectiveness of these technologies in reducing injury risk and improving athlete health. This study aims to assess the role of wearables, biomechanical analysis and AI in sports injury prevention, focusing on injury risk prediction, real-time monitoring and rehabilitation. The method used was a systematic literature review by analyzing data from peer-reviewed scientific articles, conference papers, and reports published in the last decade. The focus of this review was wearable technology, biomechanical systems, and AI applications. Data searches were conducted using related keywords, and data analysis was performed qualitatively by categorizing studies based on technology type and injury prevention goals. The results showed that wearable devices such as accelerometers and heart rate monitors can reduce micro-injuries by providing real-time physiological and biomechanical data. AI systems integrated with wearables improve the accuracy of injury risk prediction. However, the effectiveness of this technology is still limited in preventing severe injuries such as ligament tears and fractures.